THE EFFECTIVENESS OF PRIMARY SCHOOL STUDENTS' LEARNING MOTIVATION ENHANCEMENT BY SUCCESS SITUATIONS - Abzhanova, Sabila; Aitenova, Dinara; Orazbekuly, Kuandyk; Narkulova, Bakhtykyl; Nurgali, Saule (Journal of Posthumanism, 2025)
The enhancement of learning motivation in primary school students plays a crucial role in fostering academic success and personal development. This study explores the effectiveness of using success situations to enhance the learning motivation of primary school students. Success situations are defined as instances in which students experience positive reinforcement, achievement, or recognition in their academic endeavors, leading to an increase in their self-confidence and intrinsic motivation. By creating environments that emphasize achievement, this approach aims to promote a more engaged, enthusiastic, and persistent attitude towards learning.The research investigates the impact of structured success experiences on student motivation through a quasi-experimental design involving two groups of primary school students. The experimental group participated in learning activities that incorporated frequent opportunities for success, such as praise, rewards, and personalized feedback. The control group, on the other hand, engaged in traditional learning methods without specific emphasis on achievement recognition.Pre- and post-study surveys measured students’ motivation levels using a standardized motivation scale, and qualitative observations were also conducted to assess changes in behavior and attitudes towards learning. The findings indicated that students in the experimental group showed a significant increase in motivation, demonstrating higher levels of participation, persistence, and enthusiasm in academic tasks compared to the control group. Furthermore, teachers reported improved classroom dynamics and increased student engagement.This study introduces a novel approach to enhancing primary school students’ learning motivation by systematically integrating "success situations" into the learning environment—scenarios in which students are guided to experience achievable academic success through scaffolded tasks and personalized feedback. While previous research has explored intrinsic and extrinsic motivation separately, this study uniquely focuses on how structured experiences of success can directly influence students’ self-efficacy and sustained engagement, particularly among early learners. The research contributes to the field by offering an evidence-based framework that blends psychological theory with practical classroom interventions, addressing a gap in how early academic success is operationalized and measured in primary education settings.